2005
DOI: 10.1038/sj.npp.1300945
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ginseng Saponins on Enhanced Dopaminergic Transmission and Locomotor Hyperactivity Induced by Nicotine

Abstract: Several studies have shown that behavioral hyperactivity induced by psychomotor stimulants is prevented by ginseng saponins. In an attempt to investigate whether the effect of ginseng saponins is through their inhibitory action on the enhanced dopaminergic transmission by psychomotor stimulants, we examined the effects of ginseng total saponin (GTS) presynaptically on nicotine-induced dopamine (DA) release in the striatum of freely moving rats using in vivo microdialysis technique and postsynaptically on the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 49 publications
2
18
0
1
Order By: Relevance
“…16,21) The current results demonstrated that pretreatment with GTS had a strong inhibitory effect on cocaine-induced neurochemical and behavioral sensitization, which is consistent with previous studies showing that GTS suppressed the cocaine-induced conditioned place preference in mice and reduced behavioral activation induced not only by cocaine but also by other psychostimulants, such as methamphetamine, 36) morphine, 18) and nicotine. 21) Many studies have shown that pretreatment with GTS inhibited cocaine-induced hyperactivity as well as conditioned place preference in mice and the development of postsynaptic dopamine receptor supersensitivity. 16,37,38) Ginseng extract also inhibited the development of the reverse tolerance to the locomotor-acceleration effect of morphine, and the development of morphine-induced dopamine receptor supersensitivity and physical dependence.…”
Section: Fig 4 Expression Of C-fos In the Nucleus Accumbens Area Afsupporting
confidence: 91%
See 1 more Smart Citation
“…16,21) The current results demonstrated that pretreatment with GTS had a strong inhibitory effect on cocaine-induced neurochemical and behavioral sensitization, which is consistent with previous studies showing that GTS suppressed the cocaine-induced conditioned place preference in mice and reduced behavioral activation induced not only by cocaine but also by other psychostimulants, such as methamphetamine, 36) morphine, 18) and nicotine. 21) Many studies have shown that pretreatment with GTS inhibited cocaine-induced hyperactivity as well as conditioned place preference in mice and the development of postsynaptic dopamine receptor supersensitivity. 16,37,38) Ginseng extract also inhibited the development of the reverse tolerance to the locomotor-acceleration effect of morphine, and the development of morphine-induced dopamine receptor supersensitivity and physical dependence.…”
Section: Fig 4 Expression Of C-fos In the Nucleus Accumbens Area Afsupporting
confidence: 91%
“…Furthermore, they have shown that GTS inhibited the development of the postsynaptic dopamine receptor supersensitivity, 16,18,19) and blocked nicotine-induced behavioral activity. 20,21) However, the effects of GTS on cocaine-induced behavioral and neurochemical alterations have not been investigated. Therefore, in the present study, we examined whether GTS could affect repeated cocaine-induced behavioral sensitization and accumbal Fos-like immunoreactivity using immunohistochemical methods.…”
mentioning
confidence: 99%
“…When the effects of total ginseng saponins were examined on presynaptic nicotine-induced dopamine (DA) release in the striatum of freely moving rats using in vivo microdialysis technique and on the in vitro and in vivo binding of [ 3 H]raclopride to DA D 2 receptors, inhibition of nicotine-induced DA release and D 2 receptor binding was observed along with behavioral inhibition of nicotine-induced sensitization [149]. Similar results were observed with repeated cocaine administration.…”
Section: Addictionmentioning
confidence: 64%
“…Their chemical and pharmacological properties have been reported by investigators in many countries. Recently, several studies suggest that Panax ginseng (PG) and its ginsenosides can act on the central dopaminergic system [7,13]. Many studies have also reported that Panax ginseng inhibited the hyperactivity and the conditioned place preference of morphine, cocaine, and methamphetamine [9][10][11].…”
mentioning
confidence: 99%